TAZKIYATUN NAFS SEBAGAI PENDEKATAN HOLISTIK MENGATASI KECEMASAN MAHASISWA DI ERA DIGITAL INTEGRASI TASAWUF KLASIK DAN PSIKOLOGI KONTEMPORER - guefara, rahmat lutfi; El Syam, Robingun Suyud; Linnaja, Ngatoillah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
This study examines tazkiyatun nafs (soul purification) as a culturally-grounded approach to addressing student anxiety in the digital era. Contemporary university students face unprecedented challenges including information overload, social media-induced anxiety, and intense academic pressure, contributing to escalating mental health concerns. Employing a qualitative library research methodology, this study analyzes classical and contemporary Sufism literature on tazkiyatun nafs and its application to digital-age student anxiety. Findings reveal that tazkiyatun nafs encompasses three progressive stages: takhalli (elimination of negative traits), tahalli (cultivation of virtuous qualities), and tajalli (spiritual illumination). These stages provide a comprehensive framework for managing digital anxiety through: (1) digital detox as takhalli, (2) positive spiritual habit formation as tahalli, and (3) mindful awareness as tajalli. The practical contribution of this research is a tazkiyatun nafs-based spiritual guidance model integrable into Islamic higher education student well-being programs. This approach offers a holistic, culturally-resonant solution that transcends symptom reduction to foster character transformation and life reorientation toward authentic flourishing (sa'ādah ḥaqīqiyyah).